Effect of hypertension exercises on blood pressure in the elderly: A quasi-experimental study - Effendi, Erli; Febrianti, Febrianti; Nurhayati, Nurhayati; Yulianti, Retno (Science Center Group, 2024)
Background: Hypertension is a common chronic health problem among the elderly and its prevalence increases with advancing age. Non-pharmacological interventions, such as structured physical activity in the form of hypertension exercise, are recommended to support blood pressure control and improve overall well-being in older adults. Objective: This study aimed to examine the effect of hypertension exercise on blood pressure among elderly individuals and to identify factors influencing the effectiveness of the intervention. Methods: A quasi-experimental study with a pre-test and post-test control group design was conducted involving 60 elderly participants diagnosed with hypertension. Participants were divided into an intervention group and a control group. The intervention group participated in a structured hypertension exercise program for eight weeks, while the control group received no intervention. Blood pressure measurements were taken before and after the intervention period. Data were analyzed using comparative statistical tests to assess changes in systolic and diastolic blood pressure. Results: The results showed a significant reduction in both systolic and diastolic blood pressure in the intervention group compared to the control group. In addition, participants in the intervention group reported improvements in mental well-being. Social support and personal motivation were identified as important factors contributing to the effectiveness of the hypertension exercise program. Conclusion: Hypertension exercise is an effective non-pharmacological intervention for reducing blood pressure and improving quality of life among the elderly. Integrating structured exercise programs with adequate social support and medical supervision may enhance the effectiveness and sustainability of hypertension management in older adults.